Impaired comfort in children and adolescents with cancer - Tânia Alteniza Leandro; Viviane Martins da Silva; Marcos Venícios de Oliveira Lopes; Nirla Gomes Guedes; Marília Mendes Nunes; Tamires Mesquita de Sousa; Marília Viana Araújo (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To determine the strength of the association between the clinical indicators of Impaired Comfort and the evaluation sector in the hospital, age group and sex of patients with cancer. Method: Cross-sectional study, conducted in a children’s hospital, with 192 children and adolescents. For the collection, we used an instrument developed for the study. Results: The majority of the sample was male, with mean age of 11 years. The indicators most evidenced among the hospitalized patients were Crying, Report of lack of satisfaction with the situation, Report of feeling cold, and Report of feeling uncomfortable. Crying and Fear were more prevalent in children compared with adolescents, and boys were the ones that verbalized the most the Report of lack of satisfaction with the situation. Conclusion: This study enabled determining the strength of the association of the indicators of Impaired Comfort expressed by children and adolescents with cancer.